1999
DOI: 10.1159/000012340
|View full text |Cite
|
Sign up to set email alerts
|

The Amsterdam Alexithymia Scale: Its Psychometric Values and Correlations with Other Personality Traits

Abstract: Background: This article describes the construction and validation of the Amsterdam Alexithymia Scale (AAS) and explores some of the nomological net of alexithymia. Methods: Four correlational studies are presented. The internal structure of the AAS is explored by factor analyses on items. Correlations of the AAS with sex and (Guilford) intellectual abilities are established. Mean scores of three different professional groups are compared. Correlations between the AAS and several clinical and personality scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 43 publications
2
54
0
3
Order By: Relevance
“…None had medical, psychiatric, or traumatic history. Their scores on the Beck depression scale (Beck et al, 1961) and on the Bermond-Vorst Alexithymia Questionnaire (Bermond et al, 1999) were within normal ranges.…”
Section: Methodsmentioning
confidence: 86%
“…None had medical, psychiatric, or traumatic history. Their scores on the Beck depression scale (Beck et al, 1961) and on the Bermond-Vorst Alexithymia Questionnaire (Bermond et al, 1999) were within normal ranges.…”
Section: Methodsmentioning
confidence: 86%
“…Participants had no medical, psychiatric, traumatic, or sleep disorders. Their scores on Beck Depression Scale (Steer et al, 1997), Beck Anxiety Scale (Beck et al, 1988), and Bermond-Vorst Alexithymia Questionnaire (Bermond et al, 1999) were within normal range. Extreme morning and evening types, as assessed by the Horne-Ostberg Questionnaire (Horne and Ostberg, 1976), were not included.…”
Section: Methodsmentioning
confidence: 90%
“…In a study [71], it was found that recurrence of breast cancer was significantly less common in women reacting to the disease with denial or a fighting attitude than among those displaying stoic acceptance or feelings of helplessness or hopelessness. Despite more than two decades of research, alexithymia is still a controversial concept, particularly in its assessment [72], psychophysiological correlates [73]and relationships with other affective components [74, 75, 76, 77, 78]. …”
Section: Psychosocial Factors Affecting Individual Vulnerabilitymentioning
confidence: 99%